Acoustic inversions for measuring boundary layer suspended sediment processes - Thorne, Peter D.; Hurther, David; Moate, Benjamin D. (The Journal of the Acoustical Society of America, 2011)
Although sound has been applied to the study of sediment transport processes for a number of years, it is acknowledged that there are still problems in using the backscattered signal to measure suspended sediment parameters. In particular, when the attenuation due to the suspension becomes significant, the uncertainty associated with the variability in the scattering characteristics of the sediments in suspension can lead to inversion errors which accumulate as the sound propagates through the suspension. To study this attenuation propagation problem, numerical simulations and laboratory experiments have been used to assess the impact unpredictability in the scattering properties of the suspension has on the acoustically derived suspended sediments parameters. The results clearly show the commonly applied iterative implicit inversion can lead to calculated sediment parameters, which become increasingly erroneous with range, as the sound propagates through the suspension. To address this problem an alternative approach to the iterative implicit formulation is investigated using a recently described dual frequency inversion. This approach is not subject to the accumulation of errors and has an explicit solution. Here the dual frequency inversion is assessed and calculated suspended sediment parameters are compared with those obtained from the iterative implicit inversion.